2018
DOI: 10.1089/rej.2017.2005
|View full text |Cite
|
Sign up to set email alerts
|

A Screening Tool Using Five Risk Factors Was Developed for Fall-Risk Prediction in Chinese Community-Dwelling Elderly Individuals

Abstract: The objective of this study was to determine falls risk profiles to derive a falls risk prediction score and establish a simple and practical clinical screening tool for Chinese community-dwelling elderly individuals. This was a prospective cohort study (n = 619) among adults aged 60 years and older. Falls were ascertained at a 1-year follow-up appointment. Sociodemographic information, medical history, and physical performance data were collected. The mean age was 67.4 years; 57.7% were women. Female sex (odd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 24 publications
2
28
1
2
Order By: Relevance
“…In the present study, the fall rate (8.59%) was lower than those that found in other studies focusing on other countries' elderly, such as those in Australia (30%) [30], Thailand (18.7%) [31], and China (20.1%) [29]. This difference in fall incidence may be due to the fact that the fall experiences used in this study were in the last six months, rather than in the last year, as in those previous studies.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…In the present study, the fall rate (8.59%) was lower than those that found in other studies focusing on other countries' elderly, such as those in Australia (30%) [30], Thailand (18.7%) [31], and China (20.1%) [29]. This difference in fall incidence may be due to the fact that the fall experiences used in this study were in the last six months, rather than in the last year, as in those previous studies.…”
Section: Discussioncontrasting
confidence: 85%
“…These results were consistent with a falls risk assessment study conducted in Tianjin, China, with a sample of 619 subjects over 60 years old. This study showed a higher prevalence of falls associated with gender, fall history, and diabetes [29].…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Thus, physical exercises help reduce the gradual decline of physical fitness components, which can change life habits and daily routines of older adults [23]. Exercise programs are therefore important to improve or maintain physical fitness of the female elderly population, with fitness components being fundamental for predicting falls in older women [9,10,13,24]. In 2001, the American and British Geriatrics Societies [25] updated the guidelines for the prevention of falls in the elderly population.…”
Section: Discussionmentioning
confidence: 99%
“…OWD have increased risk of falls because of the simultaneously existing ageing and diabetes. Risk of falls in OWD is 2.13‐fold that of older adults without diabetes (Kang et al., 2018). Providing timely preventive interventions to forestall the act of falling could not only reduce the healthcare burden of OWD but contribute to reducing the healthcare burden of the entire older population as well, as OWD comprise a large portion of the older population.…”
Section: Introductionmentioning
confidence: 99%